Catalan contribution in the European project MEntally Disturbed Inmates Care and Support (MEDICS) - V Humet; F Cano; R Giramé; J Martín; RA Guerrero; E Turu
ABSTRACT Objective: To know the criteria of penitentiary professionals about the causes, management methods and improvement proposal, in the attention and care of inmates suffering non-serious mental disorders. Material and methods: Activity developed from March to May 2015. In Catalonia, three prisons participated. Seven different models of anonymous and written questionnaires were distributed, designed by Italy, and aimed at directors, treatment teams, correctional officers, teachers, doctors, nursing staff and volunteers. They presented the degree of participation, descriptive characteristics of groups and main answers given. To study the association between qualitative variables, the Chi squared and the exact Fisher test was used. Results: Questionnaires distributed among the 744 employees and there were obtained 174 filled (23.4%). There was more participation among health staff and treatment teams (88% and 36%). About the age of participants, doctors were the most senior group with meaningful differences (p <0.001). 40.7% were men and 57.7% women. Among the non-health staff 70% of correctional officers held a degree. Most of the total (62.4%) had their work as their main sources of knowledge about mental health. The main answers given are presented. Discussion: Almost 25% of penitentiary professionals participated in the MEDICS project. Most of them (67%) held a degree. There is a professional concern about mental disorders but not discrimination. Some groups (doctors and, specially, non-health professionals) believe as basic a continuing training and working in multidisciplinary teams.